Handbook of cultural health psychology - Kazarian, Shahe S., 1945-; Evans, David R. (Academic Press, 2001)
The Handbook of Cultural Health Psychology discusses the influence of cultural beliefs, norms and values on illness, health and health care. The major health problems that are confronting the global village are discussed from a cultural perspective. These include heart disease, cancer, HIV/AIDS, pain, and suicide. The cultural beliefs and practices of several cultural groups and the unique health issues confronting them are also presented. The cultural groups discussed include Latinos, Aboriginal peoples, people of African heritage, and South Asians. The handbook contributes to increased personal awareness of the role of culture in health and illness behavior, and to the delivery of culturally relevant health care services. Key Features * Many societies are culturally diverse or becoming so - the cultural approach is a unique and necessary addition to the health psychology area * Satisfies the ever-increasing appetite of health psychologists for cultural issues in health and women's health issues * Major and global health concerns are covered including heart disease, cancer, HIV/AIDS, pain, suicide, and health promotion * The health beliefs and practices of Latinos, people of African heritage, Aboriginal peoples, and South Asians are presented without stereotyping these cultural groups * The handbook provides excellent information for health care researchers, practitioners, students, and policy-makers in culturally pluralistic communities * References are thorough and completely up-to-date.